The Wolf’(s)-B(r)ain- The Past, Present, Future of CNS Lupus - Suhas, Murali; Parveen-Kumar, Srikanteshwara (Nepal Journal of Neuroscience, 2019)
Systemic Lupus Erythematosus is a long-studied condition with protean manifestations, yet, with so much known about the pathogenesis and treatment aspects still in the dark. In this review article, we try to sum up all the knowledge we have till date, the practice essentials used to date and the future research directions, all of which ultimately lead to a better understanding of the disease and its management.